PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 12 BUNGARAYA - Rusdel Syam; Rini Dian Anggraini; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this study is still low mathematics learning outcomes third grade students of SDN 12 Bunga Raya. This study is to improve learning outcomes math third grade students of SDN 12 Bungaraya with the application of cooperative learning model type STAD. Subjects of this study is the third grade students of SDN 12 Bungaraya Siak. The number of third grade students of SDN 12 Bungaraya at Academic Year 2015-2016 many as 32 students, consisting of 13 boys and 19 girls. This research is a class act with two siklus.Setiap cycle has four stages including planning, implementation, observation and reflection. The research instrument consists of a learning device that syllabus, lesson plans and worksheets. Results showed activity in accordance with the planning of teachers and students have also become accustomed to learning model set by the teacher. Students participate actively in group discussions. Students also were more confident to perform in front of the class. Based on the results of research and discussion, it can be concluded that the application of cooperative learning model STAD can improve the learning process and can improve learning outcomes math third grade students of SDN 12 Bunga Raya in the subject matter of measuring instruments semester of the 2015/2016 academic year.Keywords: Math Learning Outcomes, Learning Process, STAD Cooperative Learning, Action Research.